DESAIN ULANG KEMASAN PRODUK UNTUK MENINGKATKAN MINAT BELI PADA CORNER MT - Fadillah, Nur; Suastina, Andi Wa Ode (ADMIT: Jurnal Administrasi Terapan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector face increasingly intense competition, requiring the implementation of adaptive and innovative marketing strategies. One important aspect influencing consumers’ buying interest is product packaging design. Corner MT, a culinary MSME that has been operating for more than a decade, still uses a packaging design that has undergone minimal changes, which may reduce product attractiveness amid changing consumer preferences. This study aims to analyse the process of product packaging redesign at Corner MT and its implications for increasing consumers’ buying interest. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews with the owner and employees, consumer questionnaires, and documentation. The packaging redesign process was carried out using a design thinking approach consisting of problem identification, problem analysis, idea or concept development, evaluation, and implementation stages. The results indicate that redesigning the packaging from brown kraft paper to kingstruk-based packaging, combined with the use of bright colors, illustrative visual elements, readable typography, and additional business information, enhances visual appeal and forms a better perception of product quality. Consumer responses show that the new packaging is perceived as more modern, attractive, and functional, thereby encouraging higher buying interest. Therefore, packaging redesign based on the design thinking approach proves to be an effective strategy for culinary MSMEs to enhance product competitiveness.